Between Fact and Fiction in Dan Brown’s the Da Vinci Code (2003) : Reader Response Analysis - Widodo, Wahyu Unggul (TELL - US JOURNAL, 2018)
The research’s purpose is to analyze reader response strategies which are used by readers to respond Dan Brown’s the Da Vinci Code novel. The objectives of the study are to know kind of reader response strategies that are applied by the readers to respond Dan Brown’s the Da Vinci Code, to describe how the readers apply the reader response strategies on Dan Brown’s the Da Vinci Code, to describe the dominant issues raised by the readers in applying reader response strategy on Dan Brown’s the Da Vinci Code and to know why the issues are problematic. This study is a qualitative study; the primary data source of the study is the responses from amazon customers and the guest who drop responds to the Da Vinci Code novel in amazon.com. The responses which are taken are from the paperback version and it is limited to the responses which were dropped on June 10th 2006 until February 7th 2015 and the secondary data sources of the study are books, journals or any information related to reader response strategy. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows the readers use various reader response strategies to respond Dan Brown’s the Da Vinci Code. The readers apply the strategies in responding by judging, connecting, engaging, interpreting etc. The dominant issue which is raised by the reader is a debatable problem in the novel dealing with the fact and fiction, there is a great possibility it becomes a problematic because Brown’s initial statement in the beginning of the novel, “All descriptions of artwork, architecture, documents, and secret rituals in this novel are accurate.”